Managing Classroom Activities for Autistic Students in Improving English Vocabularies by Using Total Physical Response - Muhammad Andriana Gaffar; Riki Ruswandi; Wulandari Sri Wahyuni (VELES Voices of English Language Education Society, 2023)
English is one of the subjects studied in special education schools, and until now, are still many problems faced in the process of teaching this foreign language. Teachers' understanding of classroom management and appropriate learning strategies is a solution to overcome the problems that occur in learning English for children with autism. The application of the Total Physical Response (TPR) method is one of the effective methods used to learn English. The purpose of this study is to explore more information about classroom management activities and the application of the Total Physical Response (TPR) method at Satria Galdin Junior High School. The research approach used by the author is a qualitative method with a descriptive research design. Sources of data collection using interviews and observations. To analyze the data, the author uses descriptive techniques to present data based on the results of observations and interviews. The participants were selected using a purposive sampling technique. The participants of this study were students in the 2022/2023 school year, especially class VII of Satria Galdin Junior High School, as many as 20 people.  The results of this study can conclude that good classroom management supported by the application of the Total Physical Response (TPR) method in teaching English vocabulary is proven to be effective for student's mastery of English vocabulary and helps students maximize and explore their abilities. The effectiveness is seen in autistic students at Satria Galdin Junior High School.